Analisis Kemampuan Rekonstruksi Problem Solving Siswa Melalui Asesmen Higher Order Thinking (HOT) Siswa SMA - Maulani, Nofrina; Subali, Bambang (UPEJ Unnes Physics Education Journal, 2019)
Higher Order Thinking (HOT) is a high-level thinking ability. This study aims to analyze the problem solving reconstruction ability of high school students through the HOT assessment test. This research is included in Research and Development (R&D) with 3D models are Define, Design, and Develop. This study use classes X Science 1, X Science 2, X Science 3, X Science 4, and X Science 5 High School 8 Semarang Academic Year 2018/2019. Testing of research using One-Shot Case Study method. Retrieval of data in this study using test, documentation, and interview methods. The results of the feasibility test by experts obtained value of 87.08% which is included in very feasible category. While the response of students stated that students agreed to HOT assessment test with an average percentage of 70%. HOT assessment was developed in the form of reasoned multiple choice questions and each item contained four aspects to reconstruct problem solving abilities. Based on the results of this study, it was found that the HOT assessment developed contains a strategy for reconstructing problem solving abilities using four aspects: (1) recognizing problems of 92.1%, (2) strategy planning of 85.5%, (3) applying strategy of 73.7%, and (4) evaluating solutions of 50.1%.